Fundamentals and applications of fourier transform mass spectrometry - Schmitt-Kopplin, Philippe; Kanawati, Basem (Amsterdam : Elsevier, 2019)
"Fundamentals and Applications of Fourier Transform Mass Spectrometry is the first book to delve into the underlying principles on the topic and their linkage to industrial applications. Drs. Schmitt-Kopplin and Kanawati have brought together a team of leading experts in their respective fields to present this technique from many different perspectives, describing, at length, the pros and cons of FT-ICR and Orbitrap. Numerous examples help researchers decide which instruments to use for their particular scientific problem and which data analysis methods should be applied to get the most out of their data"--
includes index and bibliographical reference
Keywords: Mass spectrometry -- Methodology; Fourier transform spectroscopy